Kendo the definitive guide - Ozawa, Hiroshi; Turzynski, Angela; Yamaguchi, Tamiko (Tokyo Kodansha International, 1997)
Kendo-the way of the sword-is one of the oldest of Japan's martial arts and the one most closely associated with the samurai. Immortalized in the action movies of Akira Kurosawa and in the best selling novel Musashi, Kendo-originally a form of swordsmanship-has in recent years developed into a popular and highly competitive sport enjoyed by thousands of men and women around the world. Kendo: the definitive guide is the first book in English to provide a practical and truly comprehensive approach to the subject. Everything that the novice needs to know, from basic information about purchasing, wearing, and maintaining essential equipment to competing in international tournaments, is explained in simple, straightforward language. Step-by-step explanation of fundamental techniques needed to be mastered to attain black belt level is illustrated in easy-to-follow line drawings. With appendices giving the rules at international competitions and important information about Kendo clubs outside Japan, Kendo is the definitive guide for all non-Japanese Kendoists. A special section about the history and development of this martial art and guidelines for running practice sessions also make it a unique resource for all teachers if Kendo
Chapter 1. The basics -- Chapter 2. Stretching exercises -- Chapter 3. Waza (techniques) -- Chapter 4. Nihon kendo kata -- Chapter 5. Keiko (practice
Keywords: Kendo